Prevalence and determinants of obesity and overweight among college students of Gujarat, India: a cross sectional study - Panchal, Saurabh Naranbhai; Agrawal, Akash Virendrabhai; Thakor, Nilesh (International Surgery Journal, 2019)
Background: Early adulthood obesity itself is a predictor of adult obesity and of higher than expected adult morbidity and mortality. The objective of this study was to know the prevalence and determinants of obesity in college students of Vadodara and Patan city of Gujarat, India. Methods: The present cross sectional study was undertaken during April 2017 to March 2018 in randomly selected 5 Colleges of Vadodara city and Patan City of Gujarat. Total 1330 students between the age group of 18 to 23 years were examined and BMI were calculated. The prevalence of overweight and obesity were determined based on the International Obesity Task Force criteria. Various determinants of obesity and overweight were studied by interviewing students. Thus collected data was analyzed using SPSS 17 (Trial version). Results: Out of 1330 students, males were 49.6% Prevalence of obesity and overweight was 6.1% and 11.0% respectively. The prevalence of obesity and overweight was higher amongst less active group (6.5% and 13.4% respectively). Prevalence of obesity and overweight was significantly higher in the group of students who spent >2 hours daily in front of television or computers. The prevalence of obesity and overweight was significantly higher amongst group of students who took daily calories above recommended dietary allowance (21.5% and 22.8% respectively). The prevalence of obesity and overweight was significantly higher who took junk food (9.3% and 14.8% respectively). Conclusions: High prevalence of obesity and overweight in college students indicate an urgent need to increase awareness via education and motivation of all stakeholders.